Electric field assisted deposition of E. coli bacteria into the pores of porous silicon - Guler, Sevinc; Oruc, Cigdem; Altindal, Ahmet (ELSEVIER SCIENCE BV, 2019)
The effect of the electric field strength on the Escherichia coli (E. coli) bacteria deposition into the pores of porous silicon was investigated by impedance spectroscopy technique. The main idea behind this approach is that negatively charged E. coli bacteria can be deposited into the pores available on the surface of porous silicon upon the application of a high electric field. For this purpose, the influence of the E. coli concentration on the impedance spectra of the anodically formed porous silicon under various electric fields between 0 and 10 kV/cm was investigated. In addition, the effect of the application time of a constant electric field of 12 kV/cm on the impedance spectra of porous silicon exposed to living and dead bacterial cells was also investigated. The results reported in this study indicate that the number of live E. coli bacteria deposited into the pores of porous silicon can be controlled by the applied electric field strength. On the other hand, it was found that there is no considerable effect of the dead E. coli cell concentration on the recorded impedance spectra of the porous silicon based sensor platform.
Keywords: Porous silicon; E. coli; Impedance spectroscopy; Electric field; LABEL-FREE DETECTION; OPTICAL-DETECTION; BIOSENSORS; CRYSTAL; SENSORS; DNA; Biochemistry & Molecular Biology; Microbiology